PENGEMBANGAN MEDIA TAS BANGUN DATAR AJAIB UNTUK MENENTUKAN LUAS DAN KELILING BANGUN DATAR DI KELAS V SDN 06 SITIUNG - Zaharatul Husna; Ratnawati; Desi Karmila (LPPM Universitas Cipta Mandiri, 2025)
In mathematics learning, there is a topic entitled Exploring the World of Geometry: Area and Perimeter of Two-Dimensional Shapes. During the learning process, teachers still lack instructional media that can help students understand abstract concepts more easily. Therefore, this study developed an educational media called the Magic Flat Shape Bag to address this issue in mathematics learning. The purpose of this research is to develop the Magic Flat Shape Bag media and to produce a media that is valid, practical, and effective. This research uses a type of Research and Development (R&D) based on the ADDIE development model, which consists of five stages: (1) Analysis, (2) Design, (3) Development — at this stage, validation tests were carried out by three validators and obtained an average percentage of 78%, categorized as valid. This indicates that the Magic Flat Shape Bag media is able to deliver information accurately, appropriately, and in accordance with established standards. (4) Implementation — practicality tests were conducted by practitioners (teachers) and students, resulting in an average score of 99.06%, which is categorized as very practical. This shows that the media can be applied easily, efficiently, and suitably in real conditions without significant difficulty. Furthermore, an effectiveness test using an effectiveness sheet yielded an average score of 93.10%, classified as very effective, indicating that the media successfully supports the achievement of learning goals. (5) Evaluation. Based on the ADDIE model used in this research, it can be concluded that the Magic Flat Shape Bag media developed by the researcher is feasible to use, as it meets the minimum criteria of being valid, practical, and effective.